A comparative study of efficacy and side effects of nifedipine with nifedipine along with dydrogesterone in management of preterm labor - Singh, Sapna; Tyagi, Preeti; Anand, Deepak; Gupta, Nitika; Gupta, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preterm labor remains one of the major cause of neonatal morbidity and mortality. Different tocolytics have been studied for prolongation of pregnancy, role of progesterone in increasing latency period remains controversial. Aim of the study was to compare efficacy of nifedipine with nifedipine along with dydrogesterone as a tocolytic agent in case of preterm labor and find its impact on maternal and neonatal outcome. Methods: This study was conducted in 100 women who presented with symptoms of preterm labor, patients were then randomized to nifedipine plus dydrogesterone therapy or nifedipine treatment. Group I received Nifedipine plus dydrogesterone 10 mg and group II received only nifedipine. Results: There was significant difference in latency period between group I and group II polongation beyond 1 week was observed in 58% in group I and 32% in group II. There is significant difference in APGAR score at 1 minute and 5 minute between patients of group I and group II. In group I, 57.4% neonates have APGAR >7 whereas in group II 31.9% neonates have APGAR >7 at 1 minute. In Group I, 89.4 % neonates have APGAR >7 whereas in group II 68.1% neonates have APGAR >7 at 5 minutes. The mean birth weight in group I was 1.86 with SD 0.35 whereas in group II it was 1.72 with SD 0.34 which is statistically significant. However, no significant difference was found between admission in neonatal intensive care unit or neonatal complications and adverse effects between 2 groups. Conclusions: This study found dydrogesterone along with nifedipine is more effective as tocolytic in comparison to nifedipine alone.